Neuronal expression of a single‐chain variable fragment antibody against Aβ oligomers protects synapses and rescues memory in Alzheimer models: Nonhuman: Preclinical immunotherapeutic studies. (7th December 2020) - Selles, Maria Clara; Fortuna, Juliana; Cercato, Magali C.; Santos, Luis E; Domett, Luciana; Bitencourt, Andre L.B.; Souza, Amanda S.; Janickova, Helena; Souza, Jorge M.; Alves‐Leon, Soniza; Prado, Vania; Prado, Marco A.; et al.
Abstract: Background: Alzheimer's disease (AD) is the main cause of dementia in the elderly and is characterized by abnormal accumulation of the beta‐amyloid peptide (Aß) in the brain. Considerable evidence has shown that soluble Abeta oligomers (AßOs) are the main neurotoxins involved in synaptic dysfunction and the memory loss. Method: We evaluated the therapeutic potential of NUsc1, a single chain variable Fragment (scFv) antibody isolated from a screen to identify scFv's targeting AβOs. Using an adeno‐associated virus derived vector (AAV) we analyzed its protective effects both in vitro and in vivo models of AD. AAV‐NUsc1 capability to induce NUsc1 expression and secretion in humans was tested using human brain slices in culture. Result: We here show that recombinant NUsc1, a single‐chain variable fragment (scFv) antibody that selectively targets a subset of neurotoxic AβOs, prevented AβO‐induced inhibition of long‐term potentiation in hippocampal slices, and blocked memory impairment induced by intracerebroventricular infusion of AβOs in mice. We next developed an adeno‐associated virus vector to drive neuronal expression of NUsc1 (AAV‐NUsc1) as a novel therapeutic approach for AD. Importantly, transduction by AAV‐NUsc1 induced NUsc1 expression and secretion in adult human brain slices. In primary hippocampal cultures, transduction by AAV‐NUsc1 reduced AβO binding to neurons and prevented AβO‐induced loss of dendritic spines. Remarkably, AAV‐NUsc1 prevented memory impairment caused by AβO infusion in mice and reversed memory deficits in APPswe/PS1ΔE9 AD mice. Conclusion: AAV‐NUsc1 represents a potential tool for gene therapy in AD by using an AAV vector to induce in vivo sustained expression of a single chain variable fragment antibody to neutralize AβOs.